Religious Communication in Digital Public Sphere - Al-Zaman, Md. Sayeed (JURNAL PENELITIAN, 2020)
The interrelationship among religious communities in a particular society is complex. On many occasions, one community becomes dominant owing to several societal factors, and other communities remain on the edge. Religion in Bangladesh has a complex history. Besides, digital media as a new phenomenon has met religion recently, although this issue is often overlooked. As a result, no formal academic endeavor is seen in Bangladesh to date which focuses on the emerging digital Islamic public sphere and online religious communication. The present study tries to bridge this gap. Through careful observation of the digital public, their used contents, and produced cases of contestation, this article finds some exclusive communication patterns. First, communication among religious communities is unequal where Muslims dominate the discourse. Second, Islamic contents are more frequent in cyberspace than the contents of other religions. Third, Muslims produce digital media-based disinformation to marginalize religious minorities in both online and offline spheres.